Admission Homocysteine as a Potential Predictor for Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Zhang, Tiesong; Zhang, Luyuan; Nie, Kehui; Yang, Jun; Lou, Haiyan; Wang, Jincheng; Huang, Sicong; Gu, Chenjie; Yan, Min; Zhan, Renya; Pan, Jianwei (Frontiers in Surgery, 2022)
Background: Delayed cerebral ischemia (DCI) is a primary cause of poor prognosis after aneurysmal subarachnoid hemorrhage (aSAH) and needs a close medical attention in clinical practice. Homocysteine (Hcy) has been implicated in cerebrovascular diseases. The aim of this study was to investigate whether serum Hcy could help to predict the occurrence of DCI in aSAH patients, and compare its diagnostic value with traditional methods. Methods: We enrolled 241 aSAH patients in this study. Serum Hcy levels were collected from each patient. The baseline information was reviewed and analyzed. The binary logistic regression was used to explore the relation of serum Hcy levels with occurrence of DCI, and diagnostic performance of serum Hcy for predicting DCI was evaluated using a receiver operating characteristic curve. Results: The admission serum Hcy levels were found significantly higher in aSAH patients with DCI than those without (P<0.001). The serum Hcy levels were positively correlated with the World Federation of Neurosurgical Societies (WFNS) scores, modified Fisher scores as well as Hunt and Hess scores. Multivariate analysis revealed that occurrence of DCI was associated with serum Hcy levels (OR=1.283; 95%CI, 1.157-1.423, P<0.001), modified Fisher scores (OR=1.808; 95%CI, 1.066-3.066, P=0.028) and Hunt and Hess scores (OR=2.258; 95%CI, 1.057-4.825, P=0.036) after adjusting for the significant variables in univariate analysis. Meanwhile, serum Hcy levels achieved a good performance for DCI prediction (area under the curve, 0.781; 95%CI, 0.723-0.831, P<0.001). Conclusion: Our study showed that serum homocysteine have the potential to be a useful and cost-effective biomarker for predicting the occurrence of DCI in aSAH patients.